Rapid Screening for α-Glucosidase Inhibitors from Gymnema sylvestre by Affinity Ultrafiltration–HPLC-MS - Chen, Guilin; Guo, Mingquan (Frontiers in Pharmacology, 2017)
Gymnema sylvestre R. Br. (Asclepiadaceae) has been known to posses potential anti-diabetic activity, and the gymnemic acids were reported as the main bioactive components in this plant specie. However, the specific components responsible for the hypoglycemic effect still remain unknown. In the present study, the in vitro study revealed that the extract of Gymnema sylvestre exhibited significant inhibitory activity against α-glucosidase with IC50 at 68.70 ± 1.22 μg/mL compared to acarbose (positive control) at 59.03 ± 2.30 μg/mL, which further indicated the potential anti-diabetic activity. To this end, a method based on affinity ultrafiltration coupled with liquid chromatography mass spectrometry (UF-HPLC-MS) was established to rapidly screen and identify the α-glucosidase inhibitors from Gymnema sylvestre. In this way, nine compounds with higher enrichment factors (EFs) were identified according to their MS/MS spectra. Finally, the structure-activity relationships revealed that glycosylation could decrease the potential antisweet activity of sapogenins, and other components except gymnemic acids in G. sylvestre could also be good α-glucosidase inhibitors due to their synergistic effects. Taken together, the proposed method combing α-glucosidase and UF-HPLC-MS presents high efficiency for rapidly screening and identifying potential inhibitors of α-glucosidase from complex natural products, and could be further explored as a valuable high-throughput screening (HTS) platform in the early anti-diabetic drug discovery stage.